Leyes Internacionales de Guerra en Materia de Drones, Mercenarios y Plantas Nucleares, en la Guerra Ruso-Ucraniana - Cervantes Zárate, Santiago (2024)
This text aims to understand the changes that could be caused by the situations that occurred during the Russian-Ukrainian War in the international legislations that regulate the way of acting of the belligerent parties in conflicts. War conflicts have evolved throughout history and with them the laws that regulate them; in the case of the war in Ukraine it is no exception, due to the use of new tactics and weapons, which must be regulated. This article seeks to find out how international war legislation could change in terms of drones, mercenaries and nuclear plants. For this purpose, the qualitative approach was used as well as the deductive, exegetic and historical methods, within which the documentary technique was used. The article makes an analysis of the repercussions on international war legislation, as well as whether it is sufficient or leaves open the possibility of human rights violations, emphasizing the study of "FPV Drones", mercenaries and nuclear plants in the conflict zone. Among the conclusions, the inadequacy of the legislation is highlighted, as it allows attacks on nuclear plants.